Comparison of two biosimilarity studies of FKB327 with the adalimumab reference product: randomized phase 1 studies of single-blind, single-dose subcutaneous injection in healthy Japanese male participants - Takuma Yonemura; Rie Yazawa; Miwa Haranaka; Kazuki Kawakami; Masayuki Takanuma; Takumi Kanzo; Dimitris Stefanidis; Yasumasa Arai (BMC, 2022)
Abstract Background FKB327 has been developed as a biosimilar of the adalimumab reference product (RP). We compared the pharmacokinetics (PK), safety, and immunogenicity of FKB327 with those of the adalimumab RP after a single dose by subcutaneous (SC) injection in Japanese male participants. Methods Two randomized, single-blind, single-dose studies were conducted in healthy Japanese male participants to compare PK characteristics between FKB327 and the RP. Study 1 included 130 participants who were randomized in a 1:1 ratio to receive a subcutaneous injection of 40 mg of either FKB327 or the RP into the abdomen. In Study 2, another 130 subjects were randomized in a 1:1 ratio to receive either drug as in Study 1, but the drug administration site was changed to the thigh. The primary PK endpoints of both studies were area under the concentration-time curve from time zero to the last measurable concentration (AUC0-t) and maximum serum concentration; area under the concentration-time curve from time zero to 360 h was also evaluated as one of the primary endpoints in Study 1. Biosimilarity in terms of pharmacokinetics was determined if the 90% confidence interval of the mean difference in geometric mean ratio of all primary PK parameters was within the prespecified equivalence criteria (0.80-1.25). Immunogenicity and safety were also evaluated as secondary endpoints. Results The serum concentration-time profiles were comparable between the FKB327 and the RP treatment groups in both studies. Primary PK parameters were within the prespecified bioequivalence range in Study 2, although AUC0-t was slightly outside the upper side of the range in Study 1. No differences in safety profile were observed in these studies. The incidence of anti-drug antibodies (ADAs) and impact of ADAs on PK profile were similar among the treatment groups in both studies. Conclusion Biosimilarity between FKB327 and the RP after a single 40-mg SC injection was confirmed in healthy Japanese male participants by modifying the study design. Trial registration jRCT2071200058 (https://jrct.niph.go.jp/en-latest-detail/jRCT2071200058, https://rctportal.niph.go.jp/en/detail?trial_id=jRCT2071200058) and jRCT2071200057 (https://jrct.niph.go.jp/en-latest-detail/jRCT2071200057, https://rctportal.niph.go.jp/en/detail?trial_id=jRCT2071200057). Retrospectively registered 25/11/2020.